PENINGKATAN KONTROL DIRI SISWA TERHADAP KEGIATAN ZIKIR PAGI DAN PETANG DI SMPIT DAR EL IMAN KOTA PADANG - Ade Pajaria, Suci; Sulaiman (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to explore forms of increasing students' self-control regarding morning and evening dhikr activities. This research uses a qualitative method with a case study approach. Research data was taken through direct interviews with twelve informants, namely grade 9 (ninth) students of SMPIT Dar El Iman, Padang City. To strengthen the interview data, the researcher made observations by being directly involved in the morning and evening zikr activities. The research results showed that there were seven forms of increasing students' self-control regarding morning and evening dhikr activities. The seven forms are: i) self-control in monotheism, ii) self-control in studying, iii) self-control in being calm, iv) self-control in being optimistic and having a good opinion of Allah, v) self-control in guarding your words, vi ) self-control in maintaining health and vii) self-control in worship. The results of this research can be used as initial data for future researchers in studying different and relevant problems related to these problems.